2011
DOI: 10.1016/j.media.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput active contour scheme for segmentation of histopathological imagery

Abstract: In this paper a minimally interactive high-throughput system which employs a color gradient based active contour model for rapid and accurate segmentation of multiple target objects on very large images is presented. While geodesic active contours (GAC) have become very popular tools for image segmentation, they tend to be sensitive to model initialization. A second limitation of GAC models is that the edge detector function typically involves use of gray scale gradients; color images usually being converted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 33 publications
0
38
0
1
Order By: Relevance
“…The contour approaches [13] are widely used in practical exploitation of data from images because they effectively use specific prior information about objects and this makes them inherently efficient algorithms. Furthermore, active contours apply processing algorithms selectively to regions of the image, rather than processing the entire image [8].…”
Section: Contouring Schemementioning
confidence: 99%
“…The contour approaches [13] are widely used in practical exploitation of data from images because they effectively use specific prior information about objects and this makes them inherently efficient algorithms. Furthermore, active contours apply processing algorithms selectively to regions of the image, rather than processing the entire image [8].…”
Section: Contouring Schemementioning
confidence: 99%
“…However, implementations of the AC model have been developed for multidimensional images. [12][13][14][15] Chan et al 13 presented an extension of the original scalar image-based AC model applied to vector-valued images. Rousson and Deriche 14 also presented a vector-valued active contour.…”
Section: Previous Related Work and Motivationmentioning
confidence: 99%
“…Rousson and Deriche 14 also presented a vector-valued active contour. In a recent application to a medical imaging problem, Xu et al 15 developed a tensor gradient-based AC for use with histopathological images by computing the gradient from vectorial images. Xu et al 15 showed that the tensor gradient more completely captured the gradient information in a multichannel image than using a single channel of the image, yielding a more accurate AC scheme.…”
Section: Previous Related Work and Motivationmentioning
confidence: 99%
See 2 more Smart Citations